Angiopoietin-2 is a long-term predictor of all-cause mortality, cardiac death and sudden cardiac death in chest-pain patients with suspected acute coronary syndrome. (25th November 2020) - Aarsetoey, R; Ueland, T; Aukrust, P; Michelsen, A.E; Ponitz, V; Brugger-Andersen, T; Leon De La Fuente, R; Staines, H; Nilsen, D.W.T
Abstract: Background: Angiopoietin-2 (ANGPT2) is an important regulator of angiogenesis. Higher levels of ANGPT2 have been found to be associated with an adverse cardiovascular risk factor profile potentially reflecting maladaptive vascular remodelling including atherosclerotic plaque destabilization. Purpose: To evaluate the prognostic utility of ANGPT2 added to conventional clinical risk factors for coronary heart disease, including B-type natriuretic peptide (BNP), troponin T (TnT) and C-reactive protein (CRP), in patients with suspected acute coronary syndrome (ACS). Methods: 871 chest-pain patients with clinically suspected ACS from South-Western Norway and 982 patients from Northern Argentina were consecutively included in a prospective transatlantic cohort study. We measured plasma-concentrations of ANGPT2 in admission-samples from 1815 patients by enzyme immunoassay. Univariable- and multivariable Cox proportional-hazards models, applying both loge-transformed continuous values and quartiles (Q1–4), were fitted for the analysis of all-cause mortality, cardiac death and sudden cardiac death (SCD) within 24-month follow-up. Of the patients with suspected ACS, 838 patients had TnT release above the detection-limit of 0.01 ng/mL. We performed subgroup analysis for all-cause mortality in patients with and without TnT release. Results: Median age in the total population was 66.0 (Q1-Q3; 55.0–76.8) years and 60.4% were males. At 24-month follow-up, 254 patients (14%) had died, of which 150 (8.3%) suffered cardiac death and 76 (4.2%) SCD. ANGPT2 levels were significantly higher in patients who died compared to long-term survivors [3.87 (2.40–7.54) ng/mL versus 2.11 (1.48–3.22) ng/mL (median, 25 and 75% percentiles), p<0.001]. In multivariable analysis, ANGPT2 concentrations in the highest quartile (Q4) as compared to the lowest (Q1) were significantly associated with all-cause mortality [Hazard Ratio (HR) 1.96 (95% confidence interval (CI); 1.12–3.42), p=0.018) and cardiac death [HR 2.23 (95% CI; 1.01–4.92), p=0.047] at 24-month follow-up. For SCD, ANGPT2 concentrations in both Q3 [HR 3.59 (95% CI; 1.05–12.3), p=0.041] and Q4 [HR 3.81 (95% CI; 1.12–12.9), p=0.032] as compared to Q1 were significantly related to outcome. These results were confirmed using loge-transformed continuous values of ANGPT2. ANGPT2 was also an independent predictor of all-cause mortality in both patients with and without TnT release. For patients with TnT >0.01 ng/mL, HR for ANGPT2 in Q4 as compared to Q1 was 2.77 (95% CI: 1.41–5.44), p=0.003. For patients with TnT ≤0.01, HR for ANGPT2-Q4 was 2.67 (95% CI: 1.08–6.62), p=0.034. Conclusion: High levels of ANGPT2 were found to independently predict all-cause mortality, cardiac death and sudden cardiac death in chest-pain patients with suspected ACS, irrespective of clinical demographics, troponin-release, CRP and BNP. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Western Norway Regional Health Authority